BIM-Based Model Checking: A Scientometric Analysis and Critical Review - Sihao Li; Ziyang Jiang; Zhao Xu (Applied Sciences)
Building information modeling (BIM) has been widely applied throughout the entire lifecycle of projects in the architecture, engineering, and construction (AEC) industry. The errors in BIM models can lead to significant losses in engineering projects, thus leading to BIM-based model checking (BMC) technology garnering an increasing amount of attention. Despite numerous documents detailing the BMC process, there is a lack of systematic analysis and visualization of existing research. This study employs a combined approach of scientometric analysis and a critical review to survey articles on BMC published from 2008 to 2024 in the Web of Science (WOS) and Scopus databases. The scientific analysis objectively presents the status and evolution of this research field through quantitative data, including publications, authors, and references. Furthermore, the critical review is employed to analyze the content of the articles, summarizing the topics and challenges of current research. Finally, potential promising directions for future development are proposed.